Characterisation of silica-supported Fe–Ni bimetallic nanoparticles and kinetic study of reductive degradation of the drug nimesulide. Issue 4 (December 2016) - Gonçalves, Andressa A.; Araújo, Annelise F.; de Mesquita, João P.; Pires, Manoel J.M.; Verly, Rodrigo M.; Da Silva, Leonardo M.; Franco, Débora V.
Graphical abstract: Highlights: Silica/Fe-Ni bimetallic nanoparticles were synthesised for environmental applications. Nimesulide (NMS) was converted into a less harmful substance. It was verified a reduction of the nitro and the sulphonyl groups present in NMS. The reductive degradation reaction was strongly affected by agitation frequency. Removal of Nimesulide was affected by the Ni content present in the nanoparticles. Abstract: Ni–Fe bimetallic nanoparticle assemblies with diameter of 20–200 nm were synthesised on surface of silica and applied for reductive degradation of the drug nimesulide in aqueous solution. The bimetallic nanoparticles was synthesised as a function of the Ni content: 8 wt.% Ni + 92 wt.% Fe, 18% wt.% Ni + 82 wt.% Fe, and 34 wt.% Ni + 66 wt.% Fe. SEM images confirmed that the nanoparticles were uniformly anchored on silica. EDS analysis confirmed the presence of Fe, Ni and silica in the samples, while XRD analysis showed presence of the Fe 0 and Fe2 O3 /Fe3 O4 structures. The reductive degradation of nimesulide with silica-supported bimetallic nanoparticles containing 8 wt.% Ni was carried out under batch conditions using an agitation frequency of 250 rpm. The formation of by-products was monitored using the LC-ESI–MS technique. A complete removal of nimesulide (50 mg L −1 ) was achieved after 15 min of reaction with silica-supported bimetallic nanoparticles containing 8 wt.% Ni (6.0 g L −1 ). The influence of the external and internal mass-transfer limitations were evaluated and a theoretical analysis of the reductive reaction was presented. It was verified that the degradation of nimesulide is characterised by reduction of the nitro group and removal of the sulphonyl group with formation of an amine and thioester aromatic derivative product. The present work indicates that the reductive treatment process making use of silica-supported bimetallic nanoparticles containing Fe and Ni is very promising for the elimination of the nitro moiety present in nimesulide.